PENGEMBANGAN POTENSI DIRI SISWA MELALUI BIMBINGAN PRIBADI SOSIAL - Kholishah, Yunimar; Falah, Nailul (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
Self-potential is an ability given by Allah SWT to humans from birth. Class XI students should be able to know their own potential but lack the awareness to find out their own potential and lack the confidence to develop it. Efforts to awaken and help develop students' self-potential with the existence of personal social guidance carried out by counseling teachers at schools. Based on this background, the authors describe and analyze the personal social guidance method given by the counseling teacher to develop the self-potential of class XI IPS students at SMAN 1 Lembah Melintang. This research is qualitative research. The methods used in data collection were obtained from observations, interviews and documentation. The subjects of this study were counseling teachers and students of class XI IPS. Data analysis was carried out by compiling and processing data obtained from the field, then analyzed so that conclusions can be drawn. The validity of the data using triangulation techniques. The results of the study show that personal social guidance can help develop the self-potential of class XI IPS students, seen from the development of clients or students in participating in competitions according to their potential and participating in organizations according to their interests. Methods in personal social guidance using direct methods of individual conversations and group discussions, as well as indirect methods through mass media or school bulletins.